If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16xy + -6y = 0 Solving 16xy + -6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 16xy + -6y + 6y = 0 + 6y Combine like terms: -6y + 6y = 0 16xy + 0 = 0 + 6y 16xy = 0 + 6y Remove the zero: 16xy = 6y Divide each side by '16y'. x = 0.375 Simplifying x = 0.375
| -(z+9)+(5z+1)=-3(z+1) | | 7(5x-2)=6(6x-1) | | -5x^2=-40 | | t(n+1)=2n-5 | | 5x+34=94 | | 2x+19=72 | | 46b-10b+50= | | -2sin(2x)-4cos(x)=0 | | 2x^2-40x+96=0 | | 3t+4=2 | | 12x=1800 | | 14+6*5= | | -1.5y+4x=3 | | 5x-43=4x-11 | | 2x=5x^2-8x | | -9(t-7)-(t+3)=2 | | 6y(6y)-y+9=0 | | 30=12+2.5x | | 10=6x^2 | | 15+6(t)=81 | | 12+5a= | | .5x^2-17=145 | | 7x(7x)=4x | | 3(x+7)=2(x-(4-x)) | | 12x^2=1 | | 4x-15y=10 | | x^3+4x^2-3x+56=0 | | 3a-2bc+5a= | | 10cosx=8 | | 2(4x)+2(x)=50 | | 7+8(x-7)=7-2(x-1) | | = |